Alan Counihan - Counihan, Alan (Irish Journal of Arts Management and Cultural Policy, 2015)
Artist Alan Counihan spoke his experience tendering for public artwork commissioned by the Arts Council and other bodies and how this experience reflected both the strengths and weaknesses of Irish arts policy. The comments and points I am about to make have been shaped and experienced as a maker of art, neither as a producer of product nor as an entrepreneur, over the past 25 years. Even where critical or questioning I hope that they will be seen as constructive; it is how they are intended. We have been invited to address the fitness of purpose of current cultural structures and their responsiveness to change. I do so in light of personal engagement with cultural structures in recent times – I do not claim that they are representative.